Effects of Combustion Gas Species on Y2O3 Film Produced from EDTA·Y·H Complex by Flame-Spraying Technique. Issue 17 (2016) - Komatsu, Keiji; Sekiya, Tetsuo; Hasebe, Yasuhiro; Toyama, Ayumu; Nakamura, Atsushi; Noguchi, Masahiro; Li, Yu; Ohshio, Shigeo; Akasaka, Hiroki; Saitoh, Hidetoshi
ABSTRACT: Yttria (Y2 O3 ) films were deposited on stainless steel substrates from ethylenediaminetetraacetic·yttrium·hydrogen (EDTA·Y·H) complexes by flame spraying. The gas mixtures of acetylene-oxygen (C2 H2 -O2 ) or hydrogen-oxygen (H2 -O2 ) were used for the combustion flame and the effects of the combustion gas species on Y2 O3 films were investigated. Experiments revealed that the particles propelled in the H2 -O2 flame had lower temperature and higher velocity compared with the particles in the C2 H2 -O2 flame. The existence of Y2 O3 crystalline phases and complete decomposition of the EDTA·Y·H were confirmed. The porosity of the film was 25% when the H2 -O2 flame was used and 32% when the C2 H2 -O2 flame was used. In addition, the Y2 O3 films showed excellent adherability in tape tests. The H2 -O2 flame is thus considered suitable for fabricating dense Y2 O3 films.